2016
DOI: 10.1371/journal.pone.0150308
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Distribution Width Is Associated with Severity of Leukoaraiosis

Abstract: Red blood cell distribution width (RDW) is one of the routine hematologic parameters reported in the complete blood count test, which has been recognized as strong prognostic marker for various medical conditions, especially cardiovascular disease. We evaluated that RDW was also associated with the leukoaraiosis; common radiological finding of brain and that has been strongly associated with risk of stroke and dementia. In the present study, we included 1006 non-stroke individuals who underwent brain MRI and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 33 publications
1
21
0
1
Order By: Relevance
“…In our study, we found that RDW levels were correlated with NIHSS scores; higher RDW levels were associated with poor prognosis. Recent studies showed that elevated RDW values may cause stroke severity and independently predict future cardiovascular and allcause mortality (16,17). Our data confirmed the results of these studies and RDW levels were significantly higher in moderate to severe stroke group.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we found that RDW levels were correlated with NIHSS scores; higher RDW levels were associated with poor prognosis. Recent studies showed that elevated RDW values may cause stroke severity and independently predict future cardiovascular and allcause mortality (16,17). Our data confirmed the results of these studies and RDW levels were significantly higher in moderate to severe stroke group.…”
Section: Discussionsupporting
confidence: 91%
“…Abnormally shaped red blood cells display an increased heterogeneity in cell volume, due to impaired erythropoiesis or to excessive fragmentation or destruction. This heterogeneity, expressed as an increase in red blood cell distribution width (RDW), is associated with ischemic cerebrovascular disease ( 38 ), with increased odds of having dementia ( 39 ), with Alzheimer disease ( 40 ), and with the severity of leukoaraiosis ( 41 ). In related studies, we found indications for disturbed red blood cell aging, which is associated with changes in cell morphology, in patients with beginning demantia ( 42 ).…”
Section: Red Blood Cells and Neurodegenerationmentioning
confidence: 99%
“…Among the overall sample, 277 subjects with total WMHs (49.9%) and 321 controls (50.0%) were randomly selected for constructing ROC. With the highest Youden's index, the optimal cutoff value of 13.25% for higher RDW was identified, which was closed to 13.0% determined by the previous study (Lee et al., 2016). The remaining 278 subjects with total WMHs (50.1%) and 321 controls (50.0%) were used for further statistical analyses.…”
Section: Resultsmentioning
confidence: 65%
“…To date, though growing evidence suggests that RDW may serve as a predictor of ischemic strokes, the association between RDW and WMHs is rarely investigated. By comparing 716 controls (Fazekas scale: 0-1) with 290 severe WMHs cases (Fazekas scale: Lee et al (2016) reported that higher RDW (≥13.3%) was independently related to the severity of WMHs. In addition, an independent correlation between higher RDW and WMHs was observed in the Chinese population with acute ischemic stroke (Peng et al2017).…”
Section: Introductionmentioning
confidence: 99%